Manajemen Kurikulum Program Muadalah Kulliyatul Muballighien Al-Islamiyah (KMI) di Pondok Pesantren Al-Ishlah Bondowoso - Rika Fadilatul Laila; Nur Ittihadatul Ummah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Al-Ishlah Islamic Boarding School implements the Muadalah Kulliyatul Muballighien Al-Islamiyah (KMI) program which aims to produce muballigh who not only master religious knowledge but are also competent in da'wah and education. The program seeks to align the pesantren curriculum with the formal curriculum to ensure the quality of education is equivalent to formal educational institutions. This study aims to evaluate the curriculum management of the Muadalah program in the pesantren, focusing on the process of curriculum planning, implementation, organization, and evaluation. The method used is a qualitative approach with a case study, which involves interviews and direct observation. The results showed that Al-Ishlah Islamic Boarding School has integrated the pesantren curriculum with the national curriculum, as well as implemented relevant learning methods, such as tahfidz and yellowIslamic classic books, to equip students with in-depth religious knowledge and da'wah skills in accordance with the challenges of the times. However, challenges in the management of human resources and educational facilities still need attention to improve the effectiveness of this program.